Surgery at arterial aneurysm of vertebral artery and back-lower artery of cerebellum in the acute period of its rupture - Tsimeyko, O. A.; Moroz, V. V.; Skorohoda, I. I. (Ukrainian Neurosurgical Journal, 2009)
The analysis of surgical treatment results at 16 patients with arterial aneurysm of vertebral artery and back-lower artery of cerebellum was made. The efficiency of transcranial surgical access was proved in case of endovascular surgical interference impossibility or at high risk of complications development.